FOSTERING INCLUSIVE EFL CLASSROOMS IN MULTILINGUAL CENTRAL ASIA: STRATEGIES FOR NEURODIVERSE AND CULTURALLY DIVERSE LEARNERS IN UZBEKISTAN - Sattorova Saidabonu Shakhobidinovna (Innovate Conferences, 2025)
This article explores the development of inclusive approaches in English as a Foreign Language (EFL) classrooms within the multilingual educational context of Uzbekistan. The study focuses on effective strategies for engaging neurodiverse learners, including students with autism spectrum conditions, attention deficit disorders, and dyslexia, as well as learners from culturally and linguistically diverse backgrounds. The paper highlights the role of Universal Design for Learning, differentiated instruction, intercultural competence, and digital technologies in fostering equal learning opportunities in EFL classrooms. The findings provide practical recommendations for improving inclusive language education, enhancing teachers’ professional competencies, and supporting educational policy reforms in Uzbekistan.
Keywords: Inclusive education, EFL classrooms, neurodiversity, multilingualism, cultural diversity, differentiated instruction, Uzbekistan.